2007
DOI: 10.12973/ejmste/75399
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Reform in Turkey: A Case of Primary School Mathematics Curriculum

Abstract: The purpose of this study was to analyze the newly developed elementary school (grades 1 through 8) mathematics curriculum by considering 5 th grade students' and classroom teachers' views. The analysis of the curriculum was realized in three dimensions; (1) Classroom management -classroom physical and emotional environments, teacher and student roles, and interactions, (2) Instruction -objectives, planning, implementation, method and techniques, instructional media, and measurement and evaluation, and (3) Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 2 publications
1
26
0
6
Order By: Relevance
“…In their work with elementary teachers, they concluded that the number of students in classes and lack of appropriate materials hindered the curriculum implementation. Bulut's (2007) analysis of the newly developed elementary school mathematics curriculum also supports our findings. The author found the unsuitability of activities for crowded classrooms, a lack of infrastructure in schools and unavailability of mathematics books to be some of the weaknesses of the newly developed curriculum from the perspective of teachers.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In their work with elementary teachers, they concluded that the number of students in classes and lack of appropriate materials hindered the curriculum implementation. Bulut's (2007) analysis of the newly developed elementary school mathematics curriculum also supports our findings. The author found the unsuitability of activities for crowded classrooms, a lack of infrastructure in schools and unavailability of mathematics books to be some of the weaknesses of the newly developed curriculum from the perspective of teachers.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…They believed that the program would be beneficial for students and that it will be applied more effectively in the future. Other research also points to the positive aspects of the program (Bulut, 2007;Ozdas, Tanıslı, Kose, & Kılıc, 2005;Temiz, 2005) as being student centered; having positive reflections on students, teachers and parents; promoting learning by doing and living; encouraging teachers to develop themselves; being suitable to students' development level; setting clear goals, content, and teaching-learning process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These concerns particularly manifest themselves with respect to the issue of teachers' competency and readiness to implement the curriculum as planned by the MONE (Bulut, 2007). The results from this study suggest that teachers need support in many areas to implement the curriculum as intended.…”
Section: Discussionmentioning
confidence: 88%
“…Among many of the presented triggers, trends, problems and requirements, various new aims and goals for education in terms of the national curriculum are often identified. For example, attractive goals in curriculum reforms include active learning (Korkmaz 2008), student participation , learner-centredness (Bulut 2007, Chisholm & Leyendecker 2008, Yusuf 2013, the integration of subjects and knowledge , Priestley 2011, Wallace et al 2007, and effective learning processes (Albright et al 2013). There is also a constant effort to increase students' knowledge (Korkmaz 2008) and skills (Bantwini 2010, and to improve school achievement (Altinyelken 2010, Cheung & Wong 2011, Datnow et al 2000.…”
Section: Theory Of Change In Curriculum Reformsmentioning
confidence: 99%
“…As international studies also indicate, the counterpart of trust can be that teachers are left alone in schools to manage with change (Bantwini 2010, Chan 2010, Cheung & Wong 2011 without proper resources (Bulut 2007, Georgescu 2008, Korkmaz 2008. On the other hand, the collaborative nature of school development was noted as one of the strengths of Finnish schools, and as our results show, that crucial element of theory of change is a shared goal to increase collaboration in schools among the teaching staff, and with wider multi-professional networks and parents.…”
Section: Theory Of Change In the Finnish Contextmentioning
confidence: 99%